Directions: In this question, relationship between different elements is shown in the statements. You have to take the given statements to be true even if they seem to be at variance with commonly known facts. The statement is followed by some conclusions. Study the conclusions based on the given statement and select the appropriate answer.
1
Statements:    C < L ≤ M = E ≤ X < I,    J = X < H ≤ S ≤ V > N,    A ≤ V < T = Z = W > U
 
Conclusions:    I. L ≤ H,    II. S < M,    III. J < Z
» Explain it
B
Statements:    C < L ≤ M = E ≤ X < I,    J = X < H ≤ S ≤ V > N,    A ≤ V < T = Z = W > U
 
Conclusions:    I. L ≤ H,    II. S < M,    III. J < Z
 
Combining both the equations to find the relationship between L and H, we get
 
L ≤ M = E ≤ X < H
 
Clearly, the common sign of inequalities between L and H is of '<' and the given conclusion is L ≤ H. C1, hence, does not follow.
 
Similarly, for S and M, we get
 
S ≥ H > X ≥ E = M
 
Clearly, the common sign between S and M is of '>' and the given conclusion is S < M. C2, hence, does not follow.
 
Similarly, for J and Z, we get
 
J = X < H ≤ S ≤ V < T = Z
 
Clearly, the common sign between J and Z is of '<' and the given conclusion is also J < Z. C3, hence, follows.
 
Option B is hence the correct answer.
 
2
Statements:    C < L ≤ K = E ≤ Q < I,    J = Q < H ≤ S ≤ V > N,    A ≤ V < O = Y = W > U
 
Conclusions:    I. L < O,    II. S > K    III. O > C
» Explain it
D
Statements:    C < L ≤ K = E ≤ Q < I,    J = Q < H ≤ S ≤ V > N,    A ≤ V < O = Y = W > U
 
Conclusions:    I. L < O,    II. S > K,    III. O > C
 
Combining both the equations to find the relationship between L and O, we get
 
L ≤ K = E ≤ Q < H ≤ S ≤ V < O
 
Clearly, the common sign of inequalities between L and O is of '<' and the given conclusion is L < O. C1, hence, follows.
 
Similarly, for S and K, we get
 
S ≥ H > Q ≥ E = K
 
Clearly, the common sign between S and K is of '>' and the given conclusion is S > K. C2, hence, follows as well.
 
Similarly, for O and C, we get
 
C < L ≤ K = E ≤ Q < H ≤ S ≤ V < O
 
Clearly, the common sign between C and O is of '<' , thus C < O  or O > C and the given conclusion is O > C. Hence C3, also follows.
 
Option D is hence the correct answer.
 
3
Statements:    T < H ≤ L < S ≤ K < A,    M = F ≠ S = G ≥ I > Q,    U ≤ B < N = C = I

Conclusions:    I. N < A,    II. T < B,    III. S ≥ N
» Explain it
B
Statements:    T < H ≤ L < S ≤ K < A,    M = F ≠ S = G ≥ I > Q,    U ≤ B < N = C = I

Conclusions:    I. N < A,    II. T < B,    III. S ≥ N
 
Combining the equations to find the relationship between N and A, we get
 
N = C = I ≤ G = S ≤ K < A
 
Clearly, the common sign of inequalities between N and A is of '<'. Conclusion N < A is hence stays true. C1, hence, follows.
 
Similarly, combining equations to find the relationship between T and B, we get
 
T < H ≤ L < S = G ≥ I = C = N > B
 
Clearly, the signs are getting reversed and hence we can't define a relationship between T and B. C2, hence, doesn't follow.
 
Similarly, combining equations to find the relationship between S and N, we get
 
S = G ≥ I = C = N
 
Here the common sign between S and N is '≥' and the given conclusion is S ≥ N. Evidently , C3 follows.
 
Option B is hence the correct answer.
 
4
Statements:    A = B ≥ C > D ≤ E,    K < L ≥ N = E,    F > G ≥ B > I = J
 
Conclusions:    I. D < L,    II. D = L
» Explain it
E
Statements: A = B ≥ C > D ≤ E ,    K < L ≥ N = E ,    F > G ≥ B > I = J
 
Conclusions:  I. D < L     II. D = L
 
Combining the equations to find the relationship between D and L, we get
 
D ≤ E = N ≤ L
 
Clearly, the common sign of inequalities between D and L is of '≤'. Conclusion D < L is hence stays false individually as the relationship is D ≤ L.
 
Clearly, the common sign of inequalities between D and L is of '≤'. Conclusion D = L is hence stays false individually as the relationship is D ≤ L. 
 
But if we combine both the individual conclusions, we'll get that either D < L or D = L.
 
Hence Either C1 or C2 follows.
 
Option E is hence the correct answer.
 
5
Statements: G < T ≤ K = E ≤ Q < I,   J = Q < H ≤ S ≤ V > N,   A ≤ V < O = Y = W > U
 
Conclusions:  I. T < O     II. S > K
» Explain it
C
Statements:    G < T ≤ K = E ≤ Q < I,    J = Q < H ≤ S ≤ V > N,    A ≤ V < O = Y = W > U
 
Conclusions:    I. T < O    II. S > K
 
Combining both the equations to find the relationship between T and O, we get
 
T ≤ K = E ≤ Q < H ≤ S ≤ V < O
 
Clearly, the common sign of inequalities between T and O is of '<' and the given conclusion is T < O. C1, hence, follows.
 
Similarly, for S and K, we get
 
S ≥ H > Q ≥ E = K
 
Clearly, the common sign between S and K is of '>' and the given conclusion is S > K. C2, hence, follows as well.
 
Option C is hence the correct answer.